Dynamic Neural Network Changes Revealed by Voxel-Based Functional Connectivity Strength in Left Basal Ganglia Ischemic Stroke - Li, Qiong-Ge; Zhao, Cheng; Shan, Yi; Yin, Ya-Yan; Rong, Dong-Dong; Zhang, Miao; Ma, Qing-Feng; Lu, Jie (Frontiers in Neuroscience, 2020)
Objective This study intends to track whole-brain functional connectivity strength (FCS) changes and lateralization index (LI) in left basal ganglia (BG) ischemic stroke patients. Methods Twenty-five patients (N=25; aged 52.73±10.51 years) with five visits at <7 d, 14 d, 30 d, 90 d, 180 d and twenty-six healthy controls (HCs; N=26; 51.84±8.06 years) were examined with resting-state functional magnetic resonance imaging and motor function testing. FCS and LI were calculated through constructing the voxel-based brain functional network. One-way analysis of covariance (ANOVA) was first performed to obtain longitudinal FCS and LI changes in patients among the five visits (Bonferroni corrected, P< 0.05). Then, pairwise comparisons of FCS and LI were obtained during the five visits, and the two-sample t-test was used to examine between-group differences in FCS (family-wise error (FWE) corrected, P< 0.05) and LI. Correlations between connectivity metrics (FCS and LI) and motor function were further assessed. Results Compared to HCs, decreased FCS in the patients localized in the calcarine and inferior occipital gyrus, while increased FCS gathered in the middle prefrontal cortex, middle frontal gyrus and insula (P<0.05). The LI and FCS of patients first decreased and then increased, which showed significant differences compared with HCs (P<0.05) and demonstrated a transition at the 30-d visit. Additionally, LI at the third visit was significantly different from those at the other visits (P<0.05). No significant longitudinal correlations were observed between motor function and FCS or LI (P>0.05). Conclusion Focal ischemic stroke in the left BG leads to extensive alterations in the FCS. Strong plasticity in the functional networks could be reorganized in different temporal dynamics to facilitate motor recovery after BG stroke, contribute to diagnosing the disease course and estimate the intervention treatment.